-30 = 8x - 6
-30 + 6 = 8x
-24 = 8x
x = -3
Since x = -3 is less than 0, the solution is less than 0.
2x + 6 = 12
2x = 6
x = 3
Since x = 3 is greater than 0, the solution is greater than 0.
1 - 3x = 1
-3x = 0
x = 0
Since x = 0 is equal to 0, the solution is equal to 0.
-30 = 8x - 6
2x + 6 = 12
1 - 3x = 1
Compare the solution of each equation to 0. Determine if the solution is less than 0, equal to 0, or greater than 0.
5 answers
What is the first step when solving this equation?
3 (5x - 3) = 27
A. Distribute the 3
B. Divide by 3
C. Add 3 to both sides
D. Subtract 27 from both sides
3 (5x - 3) = 27
A. Distribute the 3
B. Divide by 3
C. Add 3 to both sides
D. Subtract 27 from both sides
A. Distribute the 3
4 (3x + 2) = 68
To solve the equation 4(3x+2) = 68, the first step is to distribute the 4 to both terms inside the parentheses:
4(3x) + 4(2) = 68
12x + 8 = 68
Now the equation becomes 12x + 8 = 68.
4(3x) + 4(2) = 68
12x + 8 = 68
Now the equation becomes 12x + 8 = 68.